On Various Communication Excelling Activities. Teaching the Skill of L istening with the Help of Different EFL Teaching Procedures - Starowicz, Diana; Polok, Krzysztof (Acta Universitatis Nicolai Copernici. Pedagogika, 2025)
Teaching the skill of listening through various methods can positively influence students’ communicative abilities. Speaking is considered to be of utmost importance in the process of teaching and learning EFL and it is essential for the students to help them be communicable in the 21st century. The aim of this paper was to present results of an study in which we made an attempt to answer the question whether students are able to enhance their speaking abilities through practicing the skill of listening comprehension via different procedures (Bottom-Up; Top-Down and Dictogloss). In the experiment we looked at three study groups of elementary school EFL students (N = 72). All the learners were Polish of similar linguistic background. In the paper we discuss the results of pre- and post-tests administered to each group of the participants.